The Role of Bone-Derived Exosomes in Regulating Skeletal Metabolism and Extraosseous Diseases - Lyu, Huili; Xiao, Ye; Guo, Qi; Huang, Yan; Luo, Xianghang (Frontiers in Cell and Developmental Biology, 2020)
Bone-derived exosomes are naturally existing nano-sized extracellular vesicles secreted by various cells such as bone marrow stromal cells, osteoclasts, osteoblasts and osteocytes, containing multifarious proteins, lipids and nucleic acids. Accumulating evidence indicates that bone derived exosomes are involved in regulation of skeletal metabolism and extraosseous diseases through modulating intercellular communication and materials transfer. Following the development of research, we found that exosome can be considered as a potential candidate for drug delivery carrier thanks to its ability of transporting molecules into targeted cells with high stability, safety and efficiency. This review aims to discuss the emerging role of bone derived exosomes in skeletal metabolism and extraosseous diseases as well as their potential role as candidate biomarkers or for developing new therapeutic strategies.